The relationship between smartphone use and cognitive function among Chinese community-dwelling older adults: the moderating role of sex - Chen, Tiantian; Foong, Hui Foh; Li, Juan; Sun, Yawen; Tang, Wei; Fu, Jiangning; Ibrahim, Rahimah; Ahmad, Siti Anom (Taylor and Francis, 2025)
This study explored the relationship between smartphone use and cognitive function among older adults in Chinese communities, integrating both self-reported and objective data. A cross-sectional survey was conducted with 209 participants aged 60 and above. The results showed that longer years of smartphone use, a greater variety of applications (apps), and the use of non-social apps was positively associated with cognitive function. In contrast, the use of social apps was linked to lower performance in certain cognitive subdomains. Hierarchical multilevel linear regression showed that years of smartphone use were a significant positive predictor of overall cognitive function. Additionally, the study identified a moderating effect of sex on the relationship between social app usage and cognitive function. Specifically, increased social app usage is associated with poorer cognitive function in men. The results indicate that prolonged and diverse smartphone use is associated with better cognitive health, while the influence of social app usage differs between sexes. The study underscores the importance of considering sex differences in future research on smartphone use and its cognitive effects in older adults.